Women's Economic Empowerment in the Democratic Republic of the Congo : Obstacles and Opportunities - World Bank (World Bank, Washington, DC, 2021)
The aim of this report is to identify binding constraints to women’s economic empowerment in the DRC and identify promising entry points to unbind these constraints. This report makes three core contributions. It provides: i) a comprehensive picture of gender gaps across the country, ii) an in-depth analysis of underlying drivers of the observed gender gaps, and iii) concrete policy and programmatic guidance on how to close the gender gaps.